ROLE OF hCG IN FOLLICULAR, LUTEAL CHARACTERISTICS, SERUM PROGESTERONE AND ESTRADIOL CONCENTRATION IN BUFFALOES - HUSSAIN, A; PRASAD, SHIV; GUPTA, H P (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted with the objective to improve conception rate through exogenousadministration of hCG (Chorulon®, lntervet India Pvt Ltd., India) on day O of estrous cycle in Murrah buffaloes.Estrus was induced using 500 μg Cloprostenol sodium im. and they were bred naturally during the observedestrus. The buffaloes in treatment group (n=10) had been given hCG@ 1500 1.U. im. and control group (n=10),,PBS@ 5ml im. on day O of estrous cycle. After 35 to 45 days of breeding the buffaloes were scanned throughu ltrasonography for the pregnancy diagnosis. Development of ovulatory follicle and the dominant follicle of 1st waveof treatment and control group was recorded. There were no significant differences in the follicular diameter betweenpregnant and non-pregnant buffaloes of treatment and control group. Development of corpus lute um (rnm2) wassignificantly (P < 0.01) greater on day 6 to 20 of estrous cycle in treatment group, while only on day 18 and 20 (P< O.o1) in control group. Serum progesterone concentration was significantly (P < 0.01) higher on days 18 and 20of estrous cycle in pregnant than non-pregnant buffaloes. The concentration of estradiol 17a found significantly (P< 0.01) lower in pregnant buffaloes on days 1, 2, 6, 10, 14, 18 and 20 of estrous cycle than non-pregnant buffaloesof treatment group. Thus it was concluded that follicular diameter of treated pregnant buffaloes were greater thanthe control pregnant buffaloes, corpus luteum of pregnant buffaloes were greater than non-pregnant, serumprogesterone concentration was higher,in pregnant buffaloes than the non-pregnant and the serum estradiol 170..was lower in pregnant than non-pregnant buffaloes.
Keywords: hCG; Follicular development; Corpus luteum; Progesterone; Estradiol; Buffalo